Video Interaktif Bagi Ibu Nifas Primigravida Sebagai Edukasi Peningkatan Motivasi Pemberian ASI Ekslusif - Sumarni, Sumarni; Karlina, Ninik (Program Studi DIV Kebidanan Fakultas Ilmu Kesehatan Universitas Muhammadiyah Gorontalo, 2024)
The quality and quantity of information are factors that influence the level of motivation of mothers in exclusive breastfeeding, therefore interactive video-based education is carried out as a means of delivering quality information and is expected to increase the motivation of mothers in providing exclusive breastfeeding. To determine the effect of interactive video-based education on increasing motivation for exclusive breastfeeding in primigravida postpartum mothers. Pre-experimental Design Method. The population in this study amounted to 50 people and the sample used was 44 primigravida postpartum mothers at RSIA Ananda Makassar City. The research instrument was a questionnaire sheet. Respondents were given interactive video-based education on the first day of the postpartum period then given video marching education a week later, then given on day 14 of the postpartum period. Univariate and bivariate analysis using the Wilcoxon statistical test. the results of the study with the Wilcoxon test obtained a value of ρ = 0.000 < α = 0.05, so that from these results there is an effect of interactive video-based education on increasing motivation for exclusive breastfeeding in primigravida postpartum mothers. the provision of interactive video-based education can be a means of obtaining quality information to increase the motivation of postpartum mothers in providing exclusive breastfeeding for their babies.